Dynamic acclimation to sunlight in an alpine plant, Soldanella alpina L. Issue 3 (3rd June 2019) - Talhouët, Anne‐Claire; Meyer, Sylvie; Baudin, Xavier; Streb, Peter
Abstract : In the French Alps, Soldanella alpina (S. alpina) grow under shade and sun conditions during the vegetation period. This species was investigated as a model for the dynamic acclimation of shade leaves to the sun under natural alpine conditions, in terms of photosynthesis and leaf anatomy. Photosynthetic activity in sun leaves was only slightly higher than in shade leaves. The leaf thickness, the stomatal density and the epidermal flavonoid content were markedly higher, and the chlorophyll/flavonoid ratio was significantly lower in sun than in shade leaves. Sun leaves also had a more oxidised plastoquinone pool, their PSII efficiency in light was higher and their non‐photochemical quenching (NPQ) capacity was higher than that of shade leaves. Shade‐sun transferred leaves increased their leaf thickness, stomatal density and epidermal flavonoid content, while their photosynthetic activity and chlorophyll/flavonoid ratio declined compared to shade leaves. Parameters indicating protection against high light and oxidative stress, such as NPQ and ascorbate peroxidase, increased in shade‐sun transferred leaves and leaf mortality increased. We conclude that the dynamic acclimation of S. alpina leaves to high light under alpine conditions mainly concerns anatomical features and epidermal flavonoid acclimation, as well as an increase in antioxidative protection. However, this increase is not large enough to prevent damage under stress conditions and to replace damaged leaves.